Remember BHP Bllliton? And their reliable LNG? Here's some news from Houston - Laetz, Hans; Ventura County Star (Ventura County Star)
Article created by Hans Laetz of Ventura County Star, reporting the BHP's semi-submersible oil platform, Typhoon, failure of not withstanding hurricane Rita. This article was forwarded from Charles Godwin to "No LNG Community Alliance" members.